Humanities Education in China: In search of Social Harmony and Chinese Nationalism - Yan Yan; Chaoyue He (International Journal of Management and Education in Human Development, 2022)
This paper explores the idea of China as a country of individuals who create the thing we call Chinese culture through the teaching of our own art, literature, and philosophy. This ideas in this paper show how interactions between social changes, social harmony, and historical memory shape school education in China. As a historical review and documentary analysis, it traces the historical development of the arts and music education and examines the Chinese government's role in such interactions over time. (online-learning.harvard.edu/course/china-humanities-individual-chinese-culture)